(untitled) (Revista Contexto & Educação, 2022)
This article presents a bibliographic review on the importance of an education focused on the perception of human beings in nature and in the production of their environment, using the resources of Geography and Environmental Education. To achieve or adopt, a bibliographic review was carried out on: the concept of the environment, environmental movements and environmental education, or the thinking of 19th century anarchist geographers and the complexity of education. The result was a vision proposal that teaches practical practices for an education that is not stuck or fragmented in the environment, but seeks to understand the environment in a complex way, through reflection on: the self and the place, the self and the society and place and society in the global context.